2014
DOI: 10.1021/ac5027435
|View full text |Cite
|
Sign up to set email alerts
|

A Mass-Spectrometry-Based Framework To Define the Extent of Disorder in Proteins

Abstract: In the past decade, mass spectrometry (MS) coupled with electrospray ionization (ESI) has been extensively applied to the study of intact proteins and their complexes, often without the requirement of labels. Solvent conditions (for example, pH, ionic strength, and concentration) affect the observed desolvated species; the ease of altering such extrinsic factors renders ESI-MS an appropriate method by which to consider the range of conformational states that proteins may occupy, including natively folded, diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
150
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(167 citation statements)
references
References 84 publications
8
150
3
Order By: Relevance
“…Increasing the activation energies also resulted in increased as the protein unfolded (results not shown), demonstrating that the proteins retain a native like conformation within our experiments. The monomeric form of α-syn is considered a natively disordered protein as it displays considerable conformational heterogeneity [35,36]. Analysis of WT α-syn before the addition of cofactors and ethanol revealed a primarily extended population (charge state ions + 8 to + 18) and a sub-population of a more compact conformational series (charge state ions + 6 to + 8) with multiple overlapping features consistent with previous data [34,37] (Figure 1).…”
Section: Resultssupporting
confidence: 86%
“…Increasing the activation energies also resulted in increased as the protein unfolded (results not shown), demonstrating that the proteins retain a native like conformation within our experiments. The monomeric form of α-syn is considered a natively disordered protein as it displays considerable conformational heterogeneity [35,36]. Analysis of WT α-syn before the addition of cofactors and ethanol revealed a primarily extended population (charge state ions + 8 to + 18) and a sub-population of a more compact conformational series (charge state ions + 6 to + 8) with multiple overlapping features consistent with previous data [34,37] (Figure 1).…”
Section: Resultssupporting
confidence: 86%
“…In addition, many of the charge states observed have higher charge than the theoretical maximal charge on spherical globular protein, as determined by the De La Mora relationship ( Z R = 0.0778 m ; for the EncFtn sH monomer Z R = 8.9) Fernandez (Fernandez de la Mora, 2000). As described by Beveridge et al, all these factors are indicative of a disordered protein (Beveridge et al, 2014). DOI: http://dx.doi.org/10.7554/eLife.18972.019…”
Section: Resultsmentioning
confidence: 94%
“…By contrast, IM-MS measurements of the monomeric EncFtn sH at pH 8.0 under the same instrumental conditions revealed that the metal-free protein monomer exists in a wide range of charge states (+6 to +16) and adopts many conformations in the gas phase with collision cross sections ranging from 12 nm 2  to 26 nm 2 (Figure 7—figure supplement 1). These observations are indicative of an unstructured protein with little secondary or tertiary structure (Beveridge et al, 2014). Thus, IM-MS studies highlight that higher order structure in EncFtn sH is mediated/stabilized by metal binding, an observation that is in agreement with our solution studies.…”
Section: Resultsmentioning
confidence: 99%
“…19 Overall, gas-phase methods appear uniquely suited to meet the challenge of describing the conformations and dynamics of flexible proteins as evidenced by the increasing number of publications in this area in recent years. [20][21][22][23][24] Nevertheless, recent studies describing the collapse of disordered structures in the absence of solvent have raised questions over the fidelity to which gas-phase methods can capture the solution conformations of these proteins. 25,26 Recent shifts in our understanding of how flexible species escape electrospray droplets during ESI also add to the complexity of describing the solution to gas-phase transfer of IDPs.…”
Section: Introductionmentioning
confidence: 99%